MV LYRAE IN THE LAST LOW STATE IN 1995-1996 - Pavlenko, E. P. (Одеські астрономічні публікації, 2017)
The detailed TV photometry of nova-like variable MV Lyr in the low brightness state covered 25 nights of observations in 1995-1996 years is made. lts brightness was B=18.m2 - 16.m2. The flash with amplitude of about 0 m. 5, lasted half an hour was detected twice in two separated nights and the sequence of similar flashes but with amplitude reached 2m was detected once. The quasi-periodic variations with typical time 0 m.13 - 0 m.14 and amplitude 0 m.1 were found.